Removal of Methylene Blue and Malachite Green by Agricultural Waste Material Stalks of Cajanus cajan - R. Deshmukh, Madhavi; M. Shah, Sapna; R. Katade, Sushama; Belhekar, A.A.; Kashalkar, R.V.; Deshpande, N.R. (Asian Journal of Chemistry, 2016)
The dyes like methylene blue and malachite green were removed by stalks of Cajanus cajan. Removal of dyes by agricultural waste was found to be comparable to the adsorbents like silica gel and graphite. The waste material was used for the removal of dyes without any chemical treatment. Sorption capacity of the stalks of Cajanas cajan for the removal of malachite green is more than for methylene blue. Sorption capacity was found to be nearly same at all the three temperatures (25, 30 and 40°C) indicating that this agricultural waste can be useful for the removal of dyes from the effluents in any season irrespective of temperature.